IDENTIFIKASI SILDENAFIL SITRAT DALAM KOPI BUBUK DAN PRODUK OLAHANNYA YANG BEREDAR DI KOTA PALU MENGGUNAKAN METODE SOLID PHASE EXTRACTION (SPE) KROMATOGRAFI LAPIS TIPIS (KLT) DAN SPEKTROFOTODENSITOMETRI: Identification Of Sildenafil Citrate in Coffee Powder And Its Processed Products Circulating In Palu City Using Solid Phase Extraction (SPE) Method Thin Layer Chromatography (TLC) And Spectrophotodensitometry - Erfan Mbealo; Qabul Dinanta Utama (Pro Food, 2022)
Coffee is a kind of beverage made from roasted and ground coffee beans. In the Regulation of the Head of  POM No. 21 of 2016 concerning food categories, and Regulation of the Minister of Industry of the Republic of Indonesia number 03/M-IND/PER/1/2016, instant coffee (pure without being mixing with other ingredients) including decaffeinated instant coffee either in retail packaging or in bulk form is required to meet the Standard National Indonesia (SNI) 2983 : 2014. As one of the food products, coffee must safe from any chemical substances that can be harmful to human health. One of the chemical substances that commonly add to instant coffee was sildenafil. This research is non-experimental descriptive of 20 samples of coffee circulating in the city of Palu which was carried out using thin layer chromatography (TLC)-solid phase extraction (SPE) and spectrophotodensitometry methods. The analysis of the results carried out is a qualitative analysis of the chemical content of the sildenafil type of drug contained in coffee products circulating in the city of Palu. Of the 20 samples tested, 3 test samples were declared positive where the retention factor (Rf) value of the test solution spot was the same as the Rf value of the standard solution spot. and spiked sample solution. Testing with Spectrophotodensitometry provides a spectrum profile and maximum absorption wavelength of the test solution spots are the same as the standard solution spots and spiked sample solutions